The role of special resolution regimes in post-crisis nancial regulation: Four Danish lessons - Carstensen, Martin B. (Politik, 2013)
In wake of the nancial crisis, the building of national and international special bank resolution regimes (SRRs) that can shut down failing banks of any size without upsetting systemic functions and putting tax- payers’ money at risk, has reached the top of the regulatory agenda. us, policy elites hope that SRRs can pose a credible commitment to counter the problem of nancial institutions being ‘too big to fail’. e article analyses the basic arguments behind SRRs and suggests that they should be viewed as political tools used by authorities in distributional battles between the nancial sector and the state. To support this argument, the Danish SRR – the rst SRR to actually have been used after the crisis – is analysed.